Richard Bancroft and Elizabethan anti-Puritanism - Collinson, Patrick (Cambridge, UK ; New York : Cambridge University Press, 2013)
"This major new study is an exploration of the Elizabethan Puritan movement through the eyes of its most determined and relentless opponent, Richard Bancroft, later Archbishop of Canterbury. It analyses his obsession with the perceived threat to the stability of the church and state presented by the advocates of radical presbyterian reform. The book forensically examines Bancroft's polemical tracts and archive of documents and letters, casting important new light on religious politics and culture"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Puritans -- England -- History -- 16th century; England -- Church history -- 16th century; Great Britain -- Politics and government -- 1558-1603.; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Relations with Puritans; HISTORY / Europe / Great Britain; RELIGION / Christianity / History; Electronic books